(untitled) (Global Journal of Human-Social Science, 2023)
One of the important areas in the interaction between human and environmental activities is waste management. In low-income countries, in this case the Democratic Republic of Congo in general and the city of Kinshasa in particular, the most common method used is uncontrolled dumping. However, if this solution is the easiest to implement and the least expensive, it is nonetheless necessary to respect certain rules in order to achieve its goal, which is very rarely the case. Throwing away garbage in inappropriate places can be extremely damaging to the environment and to human health. Within the framework of this study, observations, interviews and surveys conducted in the field with local populations as well as the sampling of physico-chemical parameters with the help of the EXTECH portable Multianalyzer, model 433201, have determined several obvious nuisances such as odors, fumes, proliferation of insects, attraction of mice and dogs. And several diseases have been noted by the presence of this pirate dump, namely, 67% of the population suffers from malaria, 17% suffers from amoebic dysentery, 10% from typhoid fever and 7% from diarrhea. This situation is particularly due to the absence of evacuation of uncontrolled dumps; the population is not better informed about the hygienic standards in terms of waste management; the absence of transit sites for the deposit of household waste; the absence of a sorting and recycling center; the lack of awareness of the population of the danger that threatens them due to the omnipresence of uncontrolled dumps; the lack of intervention and monitoring of public and municipal services in the field and the lack of political will for the establishment of waste management structures. These are the problems faced by household waste management in the city of Kinshasa in general and the commune of Kasavubu in particular.